Avaliação do desempenho anticorrosivo de um revestimento epóxi aplicado no aço galvanizado pré-tratado com silanos contendo inibidor de corrosão natural - Matheus Orlandi Pessoa (2023)
Galvanized steel is formed by layers of pure zinc and zinc alloy which influence the corrosion behaviour of this material. Galvanized steel coatings are applied to structures all over the world, providing protection that extends the useful life of the material, either by means of a barrier or cathodic protection. However, they often require additional surface treatments, such as chromium (VI), to prevent accelerated corrosion, especially in aggressive environments with high humidity or salinity. Unfortunately, the use of chromium (VI) is limited due to its toxicity to humans and environmental impact. Therefore, it is essential to develop ecological and corrosion-resistant alternatives to replace chromate-based corrosion inhibitors. For this purpose, organofunctional silane films are being studied, which are hybrid molecules that provide good corrosion resistance. Studies indicate that the addition of green inhibitors to silane solutions tends to increase the inhibitory effect of the films. After this pre-treatment, one of the most widely used ways of protecting the metal is to isolate it from the corrosive environment by applying an epoxy-based resin coating over it. In this context, this work aims to evaluate the behavior of an epoxy resin-based coating applied to the surface of galvanized steel pretreated with a silane film obtained by Tetraethoxysilane (TEOS) with γ-glycidoxypropyltrimethoxysilane (GPTMS) modified with garlic peel powder (Allium sativum L.) as a corrosion inhibitor. The anchoring effectiveness and adhesion mechanism of the organic coating based on epoxy resin was verified with the properties of the pretreatment used of the silane hybrid film with natural corrosion inhibitor. The anticorrosive performance of the coating was evaluated using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization in NaCl 3.5 wt.%. In addition, the substrate/coating and silane/epoxy interfaces were evaluated using scanning electron microscopy (SEM). The paint systems were also examined using pull-off tests. The results of the electrochemical impedance tests showed that the samples with the silane film modified with garlic extract had a better anticorrosive performance than the plates that did not have this pre-treatment applied, both coupled to the organic coating, which benefited the anchoring of the paint applied, resulting in the best anticorrosive performance of this system.